Conversational Structure Used in Guiding Conversation on YouTube Channel - I Gusti Ayu Agung Dian Susanthi; Anak Agung Istri Manik Warmadewi; Dewa Ayu Kadek Claria; I Made Astu Mahayana (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2022)
The number of followers of the account can be recovered, even it can be hundreds or thousands, the account can also be used as a model to become popular. The term for those who earn money from social networks, especially YouTube, is called as YouTuber. It becomes something interesting to study when some YouTubers uploaded their activities, one of them was the video when they went on tours or travel trips to guide the foreign tourists using English during the tours they uploaded. How the structure of the conversation they used was one of the interesting things to study. This is descriptive qualitative research which aims to describe conversational structure of tour guide in YouTube channel. The data were collected through listening, transcription, and note-taking techniques. The collected data then were analyzed using the chosen theory. The results showed that conversational structures used by tour guides in their YouTube channel include six elements which refer to opening, turn-taking, topic shift, overlapping, adjacency pair, and closing. Besides that, there are four expressions such as greeting, asking for information, giving information, and confirming. Expression of greeting consists of formal greeting. Asking for information about condition, readiness, and opinion. Giving information regarding the desire to go somewhere. Meanwhile, confirming expressions are used to ensure specific information about the guest.